The Modern Technologies of Refractive Lenticular Extraction: Comparative Analysis of Clinical and Functional Results - A. V. Doga; I. A. Mushkova; N. V. Maychuk; M. R. Obraztsova; I. S. Malyshev (Oftalʹmologiâ)
Relevance. Today, keratorefractive surgery is a high-tech branch of ophthalmology and provides a predictable, high-precision, stable and safe refractive result in patients with a wide range of refractive disorders.Purpose. To evaluate the clinical and functional results of myopia correction using the technology of fractional lenticular extraction performed using femtosecond VisuMax and LDV Z8 lasers.Materials and methods. Within the framework of this work, 160 patients (160 eyes) with inpatient myopia of medium and high degree were examined and operated, with average keratometry parameters (43.0–45.0 dptr), aged from 18 to 36 years. The follow-up period was 1 month after the operation. The SMILE group was formed: a group of patients who underwent surgery using refractive lenticular extraction technology using a femtosecond VisuMax 500 laser (80 eyes); and the CLEAR group: a group of patients who underwent surgery using refractive lenticular extraction technology using femtosecond laser Femto LDV Z8 (80 eyes).Results and discussion. Operations with SMILE and CLEAR technology were performed in the Department of refractive laser surgery of the FSAU NMIC MNTC “Eye Microsurgery” named after S.N. Fedorov of the Ministry of Health of Russia (Moscow) according to standard protocols. No intraoperative complications were recorded. The analysis of comparable clinical and functional results of myopia correction using the technology of fractional lenticular extraction performed using femtosecond VisuMax and LDV Z8 lasers was carried out.Conclusion. Thus, the analysis of the clinical and functional results of correction of myopia of medium and high degree by the technology of refractive extraction of the lenticle performed using femtosecond lasers VisuMax and LDV Z8 showed their high comparability in terms of efficiency, safety, predictability and stability. A new technology of fractional lenticular extraction using a comprehensive assessment of the condition of the ocular surface at the preoperative stage, which allows to identify and eliminate the changes that have occurred, can be recommended for widespread clinical implementation.